Os (euro)comunistas brasileiros: uma análise da trajetória política e intelectual de integrantes da chamada “corrente renovadora” (1970/1980) - Fontenelle, Marcelo (2022)
This present study aimed to analyze the trajectories of agents identified with the "renewal current" of the Brazilian Communist Party (PCB), formed in the late 1970s and early 1980s by a group of militants who were identified, among other elements, by intellectual prestige, the search for "renewal" of Marxism and the defense of democracy as a universal value. Based on a prosopographic analysis, it was highlighted the formation of a group of intellectuals with similar characteristics - the high degree of schooling and political activity through magazines and newspapers - and that had left the PCB in the early 1980s, in the midst of conflicts with the so-called "prestistas" and, later, with the “pragmatic current”. It was demonstrated that, side of the programmatic divergences, the intellectual prestige contributes to understand the exit of the PCB, once these agents had assets and resources capable of reconversion in that period of strong transformations in the political and intellectual champs. Between these agents, those who obtained greater prestige and recognition were those who ceased to be partisan intellectuals and became university intellectuals, what was done through the existence of a series of tensions because of the coexistence of them with the standard of intellectual excellence that was imposed at the time, strongly based on the North-American model of science.